RIVIEW : TINGKAT PENGETAHUAN DAN FAKTOR YANG MEMPENGARUHI KEPATUHAN MINUM OBAT ARV - iman, Sudirman; Wahyuningsih, Sri (Jurnal Buana Farma, 2025)
This review article aims to determine the level of knowledge & factors that influence compliance with taking antiretroviral (ARV) drugs in HIV patients. Human Immunodeficiency Virus (HIV) is a health problem that requires special & serious attention throughout the world.. With the high prevalence of HIV/AIDS, a good underst&ing of ARV treatment is crucial for enhancing patients' quality of life. The research method employs a literature review analyzing 15 articles from various relevant scientific sources. The results indicate a significant relationship between patients' knowledge levels & their adherence to ARV therapy. Factors such as education level, social support, availability of information, & societal stigma significantly impact adherence. Non-adherence to treatment can lead to drug resistance, making continuous education & support from healthcare providers essential. Recommendations for improving adherence include enhancing patient knowledge & providing social support. Thus, it is hoped that adherence to ARV medication can improve, contributing to better health outcomes for HIV/AIDS patients.